Visible-light-driven photocatalytic inactivation of MS2 by metal-free g-C3N4: Virucidal performance and mechanism. (1st December 2016) - Li, Yi; Zhang, Chi; Shuai, Danmeng; Naraginti, Saraschandra; Wang, Dawei; Zhang, Wenlong
Abstract: The challenge to achieve effective water disinfection of pathogens, especially viruses, with minimized harmful disinfection byproducts calls for a cost-effective and environmentally benign technology. Here, polymeric graphitic carbon nitride (g-C3 N4 ), as a metal-free robust photocatalyst, was explored for the first time for its ability to inactivate viruses under visible light irradiation. MS2 with an initial concentration of 1 × 10 8 PFU/mL was completely inactivated by g-C3 N4 with a loading of 150 mg/L under visible light irradiation of 360 min. g-C3 N4 was a robust photocatalyst, and no decrease in its virucidal performance was observed over five cycles of sequential MS2 photocatalytic inactivation. The reactive oxygen species (ROSs) were measured by a range of scavengers, and photo-generated electrons and its derived ROSs (O- 2) were found to be the leading contributor for viral inactivation. TEM images indicated that the viral particle shape was distorted and the capsid shell was ruptured after photocatalysis. Viral surface proteins, particularly replicase proteins and maturation proteins, were damaged by photocatalytic oxidation. The loss of proteins would result in the leakage and rapid destruction of interior components (four main types of RNA genes), finally leading to viral death without regrowth. Our work opens a new avenue for the exploration and applications of a low-cost, high-efficient, and robust metal-free photocatalyst for green/sustainable viral disinfection. Graphical abstract: Highlights: g-C3 N4 exhibited long-term and effective virucidal effects on MS2 virus. Photo-generated e − and its derived ROSs (O- 2) dominated viral inactivation. Viral shapes were distorted and surface proteins were damaged by oxidation. Four major types of RNA genes were severely destroyed to prevent viral regrowth.